Experimental characterization of integrated optical wireless components - O'Brien, D; Faulkner, G; Jim, K; Edwards, D; Zyambo, E; Stavrinou, P; Parry, G; Bellon, J; Sibley, M; Samsudin, R; Holburn, D; Lalithambika, V; et al. (2006)
Line of sight optical links can provide extremely high bandwidth communications between terminals, but in order to maintain alignment between transmitter and receiver, tracking is required. In this letter, we report results from a "solid-state" tracking transmitter and receiver. The transmitter consists of a custom complementary metal-oxide-semiconductor (CMOS) integrated circuit that is flip-chip bonded to a seven-element resonant cavity light-emitting diode. The receiver uses a custom seven-element InGaAs detector array that is flip-chip bonded to a CMOS integrated circuit. Results from an initial link demonstration show overall system operation at 100 Mb/s/ channel, for Manchester coded data. © 2006 IEEE.